2009
DOI: 10.1063/1.3212869
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic behavior achieved from hydrophilic surfaces

Abstract: The superhydrophobic behavior of a surface can be generally attributed to the combination of its chemical composition and microscale texture. The surface can be both hydrophobic and rough, and the roughness enhances its hydrophobicity. For a natural or artificial surface, superhydrophobic behavior is generally induced by a structured hydrophobic surface. This paper proposes an alternative; that is the superhydrophobic behavior can be obtained from a structured hydrophilic surface. The superhydrophobic behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 20 publications
0
47
0
Order By: Relevance
“…A large number of papers have focused on superhydrophobic surfaces. [32][33][34][51][52][53][54][55][56]60,61 Those studies have employed microscale patterning with hydrophobic pillars and voids where liquid did not penetrate. They are different from what we report here.…”
Section: ■ Discussionmentioning
confidence: 99%
“…A large number of papers have focused on superhydrophobic surfaces. [32][33][34][51][52][53][54][55][56]60,61 Those studies have employed microscale patterning with hydrophobic pillars and voids where liquid did not penetrate. They are different from what we report here.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Plasma-enhanced CVD (PECVD) uses plasma energy that can act to activate the precursors and/or change surface structure. [96] PECVD can be used to deposit films of PTFEtype materials to give water contact angles of > 1008 on flat substrates; if a roughened microstructure is introduced to increase the surface roughness this improves to over 1608. [97] Recent developments have demonstrated that surface roughness can be introduced during the PECVD process.…”
Section: Carbon Nanotubes (Cnts)mentioning
confidence: 99%
“…Traditionally, superhydrophobic surfaces have been fabricated either by creating rough structures on an intrinsically hydrophobic surface or by providing an additional low‐surface‐energy coating in a secondary step on top of the rough structured surface. Based on the findings reported by earlier works involving fabrication of superhydrophobic surface using an amphiphilic or hydrophilic surface, it is evident that superhydrophobicity can be achieved when two out of the three design criteria are met: (1) low‐surface‐energy material, (2) micro/nanohierarchical roughness, and (3) reentrant structures …”
Section: Resultsmentioning
confidence: 94%